2014
DOI: 10.14740/jocmr1610w
|View full text |Cite
|
Sign up to set email alerts
|

Resident Knowledge of Colorectal Cancer Screening Assessed by Web-Based Survey

Abstract: BackgroundTo evaluate resident knowledge of colorectal cancer (CRC) screening guidelines and to define areas requiring attention.MethodsA survey was created using three published guidelines for CRC screening. Program directors for internal medicine residency programs were contacted within the metro New York City area to have their residents participate.ResultsFive programs participated, and 115 responses were recorded. For the appropriate testing and interval to screen for CRC, 61/115 residents identified flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…[ 1 ] The two studies demonstrated that most physicians were aware of methods of CRC screening, but have low belief in the effect of screening on CRC occurrence, confusion about how methods of screening are performed, and insufficient information concerning the ages and frequency of screening. [ 13 14 ] Similar data specific to the primary health care community in KSA is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] The two studies demonstrated that most physicians were aware of methods of CRC screening, but have low belief in the effect of screening on CRC occurrence, confusion about how methods of screening are performed, and insufficient information concerning the ages and frequency of screening. [ 13 14 ] Similar data specific to the primary health care community in KSA is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Our study was different from previously reported ones in that, first, ours was very comprehensive and covered all aspects of CRC screening and, second, it used the novel approach of a smartphone app for education of the residents. Previously reported studies, such as that of Akerman et al [ 16 ], only tested for identification of CRC screening tests. Beyond testing for knowledge of CRC screening in average-risk patients and with a family history of CRC, we also tested the important concept of differentiation between prevention and detection tests, which is acknowledged in the ACG and ACS guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for this lack of improvement in CRC screening could be residents’ deficient knowledge about CRC screening, even though guidelines from the American College of Gastroenterology (ACG), ACS, and US Preventive Services Task Force (USPSTF) are mostly in agreement about screening modalities and age [ 13 - 15 ]. Akerman et al [ 16 ] assessed residents’ CRC screening knowledge via a Web-based survey and concluded that there were many deficiencies. They concluded that fecal occult blood testing for screening purposes remains undervalued, and confusion about administering the test persists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 These numbers were comparatively higher from several systematic studies in the Arab world. 11 Studies have shown that a low rate of physician recommendations [12][13][14] or patient's unawareness of the disease burden 12 often accounts for a low compliance rate as the main reasons for the increased incidence. Furthermore, at the medical residents' level, studies have shown that the compliance to colorectal cancer screening is even poorer.…”
Section: Introductionmentioning
confidence: 99%